Strategi Peningkatan Loyalitas Anggota KUD: Perspektif Harga, Keragaman Produk, dan Faktor Budaya - Didit Darmawan; Wafiq Nurazizah (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this observation is to invite factors that are influenced by loyalty. Literature Survey Marketing management. The method of writing this research paper is quantitative method and the research sample is residents around Pujon District, Malang Regency. Organizational culture affects management loyalty. Basically, this cooperative aims to improve the management of members and society as a whole. Although cooperatives do not prioritize profits, cooperative efforts can maintain their survival and increase their business continuity. The first goal of the establishment of cooperatives is to motivate the national economy to ensure the welfare of its members and has expanded the establishment of cooperatives to date. To help its members, cooperatives must improve their operations. This study also uses a questionnaire method that must be filled in at least 100 respondents of KUD members. The form must be filled in on the website that has been done by the cooperative on behalf of the village unit cooperative.